2020
DOI: 10.1016/j.ijcha.2020.100598
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in subclinical vascular function in South Asians, Whites, and African Americans in the United States

Abstract: Background South Asians are a high-risk ethnic group for cardiovascular disease despite having lower levels of conventional cardiovascular risk factors such as obesity and smoking. Ethnic differences in pulse wave reflections, arterial stiffness, and subclinical atherosclerosis as measured using augmentation index (AIX), pulse wave velocity (PWV), and carotid intima-media thickness (CIMT) may reflect some of this excess risk. Methods We conducted a cross-sectional analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Notably, this review also reported that other CVD risk factors are not or only modestly related to cf-PWV, an observation that matches our findings. We add the insight that the association between age and central stiffness was not ethnicity-dependent, which agrees with the American study [ 3 ] but disagrees with the Dutch study [ 26 ]. In the latter study, the positive relation between age and cf-PWV was significantly greater for the South Asian group than for the Dutch group, resulting in a greater cf-PWV difference between ethnicities at higher age.…”
Section: Discussionsupporting
confidence: 67%
“…Notably, this review also reported that other CVD risk factors are not or only modestly related to cf-PWV, an observation that matches our findings. We add the insight that the association between age and central stiffness was not ethnicity-dependent, which agrees with the American study [ 3 ] but disagrees with the Dutch study [ 26 ]. In the latter study, the positive relation between age and cf-PWV was significantly greater for the South Asian group than for the Dutch group, resulting in a greater cf-PWV difference between ethnicities at higher age.…”
Section: Discussionsupporting
confidence: 67%
“…Other studies utilizing the SphygmoCor CvMS device reported comparable effects of age on cfPWV measurements ranging from: 0.2 m/s per 10 years ( 58 ), to 0.3–0.4 m/s ( 59 ), to somewhat larger effects of around 0.7–0.9 m/s reported by the same group of authors ( 16 , 60 ). While age was identified as the strongest determinant of PWVao too ( 61 ), studies that investigated factors influencing Arteriograph’s PWVao measurements did not reported comparable, unstandardized regression metrics.…”
Section: Discussionmentioning
confidence: 58%
“…Sex, with higher values of PWVao in women compared to men, was also identified as significant factor in another study investigating Arteriographs’ PWVao measurements ( 61 ). However, while reports on the relationship between sex and central PWV measurements that were taken by devices other than Arteriograph were varied, all studies including those utilizing oscillometric devices reported either greater values of central PWV in men ( 16 , 59 , 60 , 62 , 76 78 ) or no association with sex ( 69 , 79 82 ). Thus, it appears that higher values of PWVao measurements in women may be specific to Arteriograph device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 Ethnic differences between South Asians, White patients, and Black patients living in the United States showed higher pulse wave reflections in South Asians, a marker of arterial stiffness. 46 Further investigation is needed to determine the optimal medical management in patients with subclinical atherosclerotic disease and its effect on long-term cardiovascular outcomes.…”
Section: Modifiable Risk Factors: High Carbohydrate-to-protein Intake...mentioning
confidence: 99%